Noções de inconsciente no século XIX: tradições pré-psicanalíticas e sua relação com a obra freudiana - Braga, Thiago Estivalet (2022)
Freud is often singled out as the figure responsible for the "discovery" or "creation" of the Unconscious. Looking at the status quo of psychology and philosophy in the course and precedents of the 19th century in German-speaking countries, one realizes that the question of the unconscious is pressing within certain debates. The present paper intends to establish a panoramic bibliographical review of the ways in which the concept of the unconscious was used in this period, pointing out several traditions in which the appearance of the notion of the unconscious emerges with distinct purposes. From this we discuss Freud's notion of unconscious, aspects of his conception of science, and the way in which his work fits into this broader, earlier context of discussion about the unconscious. We identify that the notion of unconscious that pervades the discussions in the German nineteenth century are a philosophical development of the polemic between determinism and freedom, the unconscious assuming one of these two positions: to ensure the possibility of a deterministic science of the psyche or to ensure the conditions of possibility to affirm the autonomy of the subject. The present paper analyzes Freudian theorizing about the unconscious against this background. We believe it is important to discuss Freud's place in the history of the development of the concept and the role it plays in his work